Evaluation of the thermodynamic analysis of hydrogen production from a middle-temperature intensity solar collector, a case study. (29th August 2022) - Karabuga, Arif; Yakut, Melik Ziya; Utlu, Zafer
Abstract: In today, the basic necessity for the economic and social development of countries is to have a cheap, reliable, sustainable, and environmentally friendly energy source. For this reason, renewable energy sources stand out as the most important key. Solar energy-based multi-energy generation systems are one of the most important options among the current scenarios to prevent global warming. In this presented study, electricity and hydrogen production from a solar collector with medium temperature density is investigated. In this system, 34 pipes evacuated tube solar collector (ETSC) is used for thermal energy generation, organic Rankine cycle (ORC) for electricity generation, and Proton exchanger membrane electrolyzer (PEMe) for hydrogen production. In addition, the energy and exergy efficiencies of the whole system calculated as 51.82% and 16.30%, respectively. Moreover, the amount of hydrogen obtained in PEM is measured as 0.00527 kg/s. Highlights: A green hydrogen production and thermodynamic assessment are proposed. The overall energy and exergy efficiency of the hydrogen production system is calculated as 51.82% and 16.30%, respectively. The amount of hydrogen obtained in PEM is measured as 0.00527 kg/s. The exergy efficiency of ETSC, ORC, and PEMe components are calculated as 4.40%, 18.83%, and 4.87%, respectively.